TOWARDS A METHODOLOGY FOR ANALYZING STRUCTURAL CHANGES AND REFORMS AT THE REGIONAL LEVEL - GRES, Arsen (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study focuses on the issues of shaping and implementing an effective regional policy aimed at sustainable and balanced development of the region as a socio-economic system. The purpose of the article is defined as the generalization and further development of methodological and applied foundations for analyzing structural changes and reforms at the regional level. It is concluded that the formation of a methodology for analyzing structural reforms is one of the most complex tasks within the functions of regional structural policy. It is emphasized that such a methodology, by definition, cannot be uniform across different regions and under varying external and internal conditions, and therefore requires the application of a systematic and comprehensive approach, particularly in relation to all possible aspects of analysis. It is shown that constructing an optimal and rational system of economic analysis in this case requires adherence to several fundamental aspects. First, it involves taking into account all directions (components) of the processes of structural reform in the regional economic system. Second, it requires building an analysis and evaluation algorithm that sequentially covers the following stages of research: identification and characterization of structural imbalances in the regional economy in the context of emerging challenges for the region’s economic and social development; assessment of macroeconomic prerequisites for structural changes under conditions of crisis and post-war recovery; analysis of investment and innovation factors of structural dynamics in the regional economy; characterization of the institutional environment of structural reform; generalization of the analysis results and formulation of conclusions regarding critical imbalances and obstacles to reforms, priorities of institutional changes and structural modernization, as well as the system of mechanisms and instruments for regulating structural-dynamic processes. Third, it presupposes the application of the most appropriate methods of economic analysis at each corresponding stage of analytical work.